Environmentally weathered residues source diagnostic by high-molecular-weight polycyclic aromatic sulphur heterocycles. Issue 15 (7th December 2016) - Hegazi, Abdelrahman H.; Fathalla, Eiman M.; Andersson, Jan T.
ABSTRACT: High-molecular-weight polycyclic aromatic sulphur heterocycles (HMPASH) were applied in a forensic chemical analysis to identify the source(s) of environmentally weathered residues polluting the beaches of the Mediterranean city of Alexandria, Egypt, and to assess their weathering trends. The HMPASH were investigated by Fourier transform ion cyclotron resonance mass spectrometry in residues and an Egyptian crude as a possible source oil. The dibenzothiophenes/naphthenodibenzothiophenes (DBE 9/DBE 10) parameter indicated that two studied residues were likely to have originated from Egyptian crude oils, whereas the third residue could have had a foreign source. The residues displayed different stages of weathering. HMPASH having double bond equivalent (DBE) 1–5 were more influenced by weathering processes than those having DBE 6–17, probably because they are aliphatic sulphides and not aromatic compounds.